ROZWÓJ INSTYTUCJI TRUSTU W PRAWIE SZKOCKIM - Stępkowski, Aleksander (Zeszyty Prawnicze, 2017)
Development of the Law of Trusts in Scotland Summary The earliest indisputable traces of trusts law in Scotland may be found in reports from the first half of the XVH‘h century. There are several examples of even earlier dispositions to which a fiduciary character might be ascribed, coming from the XV,h and XVTh centuries. Nevertheless, we are not able to state categorically that these represent examples of trusts, since there is nothing about priority of beneficiary's rights in respect to trust property, before trustee’s personal creditors, whereas it seems to be today differentiam specificam discerning trust from contractual relations. According to the aforementioned case law, the main subject of trust dispositions was land (immoveable property, called in Scotland “heritable”). The main issue giving rise to legal controversies was the question of the manner in which the existence of a trust in land was allowed to be proved. The rules of evidence adopted by the Court of Session differed substantially from those of Scottish land law which were usually applied when proving titles in land. According to Scottish institutional writers, it seems to be most probable that the reason for such a favourable standing of land being subject to trust was that the Court of Session proceeded on the ground of its’ nobile officium, extraordinary equitable jurisdiction performed by this court, most probably since the very early stages of it’s activity, on the basis of a statutory provision from 1540. During the XVIIth century the first statutory regulations concerning trusts appeared, but more substantial progress in this respect took place in the XIXth century. Most often, it was statutory implementation of earlier common law principles and, in relation to trustees’ competences, of standards relating to the professional drafting of trust deeds. XIXth century legislation was consolidated in 1921 as the Trusts (Scotland) Act 1921 which was subsequently amended in 1961 and, together with the British Trustee Investments Act 1961 (which is still in force in Scotland although will be repealed soon, as it was already done in England in 2001), is partial codification of Scottish trusts law. Nevertheless it should be emphasised that Scottish trust law is still principally based on case law. As regards the influence of English Equity on the development of the Scottish law of trusts, it seems to be negligible in the early stage of the latter’s development. A considerable influence of the Chancery Court’s cases upon Scots law in respect of trusts only began in the fourth decade of the XIXth century, with a book by Charles Forsyth ( The Principles and Practice o f the Law o f Trusts and Trustees in Scotland (1844)), who had used intensively English case law as an illustration, he claimed, of Scottish law principles. Since this publication, nevertheless, English case law, as exposed in English textbooks, though not necessarily in the Chancery Reports, became an important source of inspiration for Scottish lawyers writing books on this subject and, subsequently, it was also used in the Court of Session as an important source of authority. Notwithstanding the above, Scottish judges were always more critical and generally have applied English principles in a less willing manner than has been seen from Scottish advocates and solicitors. Generally speaking, the English influence, although considerable, has not changed the very construction of Scottish trusts law. A beneficiary’s claim in respect of trust property is still considered to be a personal right, as opposed to a sui generis right in real estate. Contemporary Scottish jurisprudence considers trust property as a trustee’s special patrimony, distinct from his general patrimony and, as such, not accessible by his personal creditors. In this way, the Scots have worked out a civil law approach to trust, which was long considered to be hardly possible. This is also a reason why Scottish trusts law, as well as the whole of Scottish law, attracts so much attention from lawyers from Continental Europe.